PT. Smart Finance's Design Of Green Budgets - Natania Kristi Keru; Frety Maong; Febrina Graca Peruge (Proceeding of The International Conference on Business and Economics, 2023)
This century has seen an increase in the development of sustainable development, and to help with this, the green economy strategy has been established. Businesses who are aware of this are beginning to include environmental management components to the strategic roadmap in order to accommodate this programme, which needs funding in order to be carried out. As a result, many institutions are now beginning to use green budgeting techniques. A budgeting model known as "green budgeting" gives environmental considerations top priority during the planning, execution, monitoring, and assessment stages. Organisations can use budgets as a tool to promote the accomplishment of environmental goals by implementing green budgeting. The OECD-based green budgeting theory and idea is applied. The purpose of this study is to offer a framework for implementing the green budgeting idea in line with business needs. This study employs qualitative methodologies grounded in financial company case studies. The information used came from documents and interviews pertaining to the organisation's green corporate roadmap and budgeting procedure. The study's findings demonstrate that PT. Smart Finance has strategic goals for environmental management in its frame design, and these goals are guided by the company's long-term aims and its shareholders. The company has relevant policies, such as the Green Company Document Blueprint, to put this idea into practice. It also has media, such as management reports and sustainability reports, to report on its progress and provide information on programme realisation. If this idea is put into practice, the annual budget of the company will need to be prepared with a grading system for environmental management.